Enhancing turnaround maintenance in process plants through on-stream phased array corrosion mapping: a review - Tai, Jan Lean; Sultan, Mohamed Thariq Hameed; Łukaszewicz, Andrzej; Shahar, Farah Syazwani; Oksiuta, Zbigniew; Krishnamoorthy, Renga Rao (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This review paper aims to understand the current processing plant maintenance systems and further identify on-stream phased array corrosion mapping (PACM) to reduce turnaround maintenance (TAM) activity during plant operations. Reducing the TAM duration and extending the TAM interval are common goals of most researchers. Thus, a detailed review was performed to understand the maintenance systems and the problems faced. Furthermore, a review of the current PACM application and the possibility of applying it during on-stream inspection was also performed. PACM has better detectability for localized corrosion, and the results can be obtained for a range of thicknesses, which is the main advantage of this method. However, applying PACM during on-stream inspections at elevated temperatures presents challenges owing to the limitations of the ultrasonic properties and increased probe contact. Future research is needed to evaluate the effectiveness of PACM on piping systems that can be utilized for inspection during plant operation at elevated temperatures. This will enable the detection of general and localized corrosion in common materials, thereby reducing the TAM duration and extending TAM intervals. Detecting and monitoring corrosion growth without shutdown is critical for ensuring the safety and reliability of the processing plants. This literature review provides a more precise direction for future research to address these challenges and to advance the field of on-stream corrosion monitoring.